Pachybasin, a Major Metabolite from Culture Broth of Endophytic Coelomyceteous AFKR-18 Fungus isolated from a Yellow Moonsheed Plant, Arcangelisia flava (L.) Merr. - DEWI WULANSARI; YULIASRI JAMAL; . PRAPTIWI; ANDRIA AGUSTA (Bogor Agricultural University, Indonesia, 2014)
Endophytic fungi have been known to produce a broad range of biologically active secondary metabolites. One endophytic filamentous fungus, Coelomycetes AFKR-18, isolated from the young stems of a yellow moonsheed plant, Arcangelisia flava, has been found to produce pachybasin when placed in a liquid medium. The chemical structure of pachybasin was deduced from MS, 1D-, 2D-NMR spectrum analysis, and from reference data. On a micro-dilution test, pachybasin showed antimicrobial activities against E. coli, B. subtilis, M. luteus, S. cerevisiae, C. albicans, A. niger, and A. flavus, with MIC values of 64.0 µg/mL, and against S. aureus and F. oxysporum with MIC values of 32.0 and 16.0 µg/mL respectively.